Potassium ameliorates cotton (Gossypium hirsutum L.) fiber length by regulating osmotic and K+/Na+ homeostasis under salt stress. Issue 1 (17th January 2023) - Yu, Kai; Ju, Feiyan; Wang, Zhuo; Sun, Liyuan; Huo, Yuyang; Zhu, Junjun; Pang, Jiali; Ali, Saif; Chen, Weiping; Wang, Shanshan; Zhou, Zhiguo; Tang, Qiuxiang; et al.
Abstract: Potassium (K) application can alleviate cotton salt stress, but the regulatory mechanisms affecting cotton fiber elongation and ion homeostasis are still unclear. A two‐year field experiment was conducted to explore the effects of K on the osmolyte contents (soluble sugar, K + content, and malate) and related enzyme activities during the fiber elongation of two cotton cultivars with contrasting salt sensitivity (CCRI‐79; salt tolerant cultivar, and Simian 3; salt‐sensitive cultivar). Three K application treatments (0, 150, and 300 kg K2 O ha −1 ) were applied at three soil salinity levels (low salinity, EC = 1.73 ± 0.05 dS m −1 ; medium salinity, EC = 6.32 ± 0.10 dS m −1 ; high salinity, EC = 10.84 ± 0.24 dS m −1 ). K application improved fiber length and alleviated salt stress by increasing the maximum velocity of fiber elongation ( V max ). The increase rate of K on fiber length decreased with elevating salt stress, and the increase rate of K on V max of CCRI‐79 was greater than that of Simian3. K application can increase the enzyme activities (phosphoenolpyruvate carboxylase, PEPC, E.C. 4.1.1.31; pyrophosphatase, PPase, E.C. 3.6.1.1; and plasma membrane H + ‐ATPase, PM H + ‐ATPase, E.C. 3.6.3.14) as well as the content of osmolytes associated with the enzymes mentioned above. K increased the osmolyte contents under salt stress, and the increase in the K + content of the fibers was much higher than that of soluble sugar and malate. The results of this study indicated K fertilizer application rates regulate the metabolism of osmolytes in cotton fiber development under salt stress, K + is more critical to fiber elongation.